PROJECT BASED LEARNING: INNOVATIVE EDUCATION-BASED APPROACH IN ECONOMICS AT SMKN 2 BLITAR - Fatimah, Siti; Forijati, Forijati; Subagio, Subagio (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
Interest in online entrepreneurship is still small, only 2% of students have started online entrepreneurship. Online business learning gives students confidence to be interested in online entrepreneurship in accordance with the knowledge and practice of online business skills. This research examines in more depth the application of project based learning (PjBL) development in online business learning. The research method used is a quantitative descriptive method. First, the researcher conducted literature research to gain an understanding of the concept of PjBL and online business learning. Next, the researcher created a project to be taught to students in online business learning. The results of the research before being revised towards the learning model were very valid by obtaining a total score of 26 with a percentage of 87% located in range 81%-100%, so the learning model is ready to be used. Project-based learning becomes more focused on real-world experiences once implemented. The project-based learning model is one of the learning models that is quite effective to be developed in the world of education today. This model allows students to apply the knowledge they have learned through the various thinking skills, attitudes and concrete skills they have. By actively involving students in the learning process, this model can increase student engagement and enable them to better understand the concepts being studied. Apart from that, the project-based learning model is also very suitable for solving complex problems faced in the real world. Through learning through investigation, collaboration, and experimentation in creating a project, students can learn to think critically and creatively in solving complex problems. The use of a project-based learning model can provide great benefits in developing students' skills and understanding